The Impact of Financial Condition, Audit Tenure, Profitability, and Opinion Shopping on Going-Concern Audit Opinion - Ghardini, Annisa; Yusralaini; Safitri, Devi (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
The aim of this study is to evaluate and experimentally demonstrate the impact of financial conditions, audit duration, profitability, and opinion shopping on the going concern opinion. The research employs numerical methodologies and secondary sources of information to examine the population of mining enterprises listed on the Indonesia Stock Exchange among 2017 until 2021. The sample in this research was 25 mining companies within 5 years, with purposive sampling as a technique for taking the sample. In the analysis process, this study used logistic regression. The results showed that financial condition variables had a partial impact on going-concern audit opinion. However, audit tenure, profitability, and opinion shopping have not been significantly impacted on going-concern assessment. It is hoped that this research can subsequently be used to develop theory related to going-concern audit opinion and may be applied by companies and independent auditors to improve understanding of the factors that impact these opinions. Keywords: Audit Tenure; Financial Condition; Going-Concern Audit Opinion; Opinion Shopping; Profitability.